Aligning Islamic Financing and the SDGs in Buy Now Pay Later: A Maqasid Based Shariah Governance and Audit Framework - Moch Rusli (UIN Raden Mas Said Surakarta, 2026)
This study developed an operational shariah governance framework for Buy Now Pay Later (BNPL) products by integrating AAOIFI, IFSB, and DSN–MUI standards through a Design Science Research (DSR) approach. It produced three audit-ready artifacts: a Maqasid–SDGs compliance matrix, a murābaḥah bi al-taqsīṭ contract blueprint, and an audit checklist. Documentary data from shariah governance standards and publicly available information from three anonymized Islamic BNPL providers were analyzed using deductive content analysis, blueprint walkthroughs, matrix scoring, inter-coder reliability testing, and a mini-Delphi for content validation. The findings show moderate to high compliance, with ḥifẓ al-māl consistently strong, while al-ʿadl and ḥifẓ al-ʿaql remain weaker due to deficiencies in late-fee charity management, ownership and risk verification before resale, and explicit anti-compounding controls. In contrast, price transparency and margin disclosure were generally robust. This study operationalizes maqāṣid al-sharīʿah into measurable indicators aligned with SDGs 1, 8, and 12, providing a practical governance and audit framework for regulators, auditors, and Islamic fintech providers.